2010
DOI: 10.1007/s12034-010-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of 5d transition metal mononitrides and monoborides using density functional method

Abstract: 5d-metal mononitrides and monoborides viz. X-N and X-B (X = La, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg) are studied using density functional method based B3LYP functional with LANL2DZ and SDD basis set. The lowest spin state, electron affinities, ionization potentials and binding energies for mononitrides and monoborides are obtained. The electronic state and electronic configuration of mononitrides and monoborides are discussed. Orbitals involved in bond formation are identified. The properties of mononitrides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…The difference is also obvious, as all the B lines are parallel to each other in oC8-WB, while this pattern is interrupted by one perpendicular B chain between each pair of parallel B lines in tI16-WB (Lundstrom, 1985). Kalamse et al (2010) studied the atomic charges from Mulliken and natural orbital population analysis for 5d transition metal mononitrides and monoborides. They found that W can accept one electron from a B atom to half-fill the 5d orbital, and the bonding characteristic in 5d metal monoborides is of a covalent ionic character with dominant covalent characteristics, as B has a +1 oxidation state.…”
Section: Wbmentioning
confidence: 99%
“…The difference is also obvious, as all the B lines are parallel to each other in oC8-WB, while this pattern is interrupted by one perpendicular B chain between each pair of parallel B lines in tI16-WB (Lundstrom, 1985). Kalamse et al (2010) studied the atomic charges from Mulliken and natural orbital population analysis for 5d transition metal mononitrides and monoborides. They found that W can accept one electron from a B atom to half-fill the 5d orbital, and the bonding characteristic in 5d metal monoborides is of a covalent ionic character with dominant covalent characteristics, as B has a +1 oxidation state.…”
Section: Wbmentioning
confidence: 99%
“…For the upper state of our observed transitions, due to the situation that there is large spin-orbit mixing of the excited states in PtB, the electronic state are only labeled by their value. It is a difficult task to work out the electronic configurations of upper states giving rise to the observed = 1/2 and 3/2 states; however, a simple consideration of promoting one electron from the ground configuration to various higher energy MOs gives many configurations that could be responsible for the = 1/2 and 3/2 states as indicated in configurations (4), (5), and (7).…”
Section: Electronic Configurations and Electronic Statesmentioning
confidence: 99%
“…Kalamse et al 7 using density functional method based B3LYP functional with LANL2DZ and SDD basis set calculations predicted the ground state bond length and vibrational frequency of PtB to be 906 cm −1 and 1.809 Å, respectively. The vibrational separation is in good agreement with our determined value of 903.6 cm −1 , but the bond length is very different from our 1.741 Å.…”
Section: Electronic Configurations and Electronic Statesmentioning
confidence: 99%
“…Следует отметить, что, несмотря на существенные усилия экспериментаторов, была успешно изготовлена только ограниченная группа боридов тяжелых 4d-, 5d-металлов. С теоретической точки зрения к сегодняшнему дню проведен широкий набор расчетов для прогнозирования свойств этих боридов, но большинство из них были посвящены моноборидам [11][12][13][14][15] или диборидам [16][17][18][19][20][21][22][23] тяжелых переходных металлов. Гораздо меньше информации имеется о вышеупомянутых тетраборидах MB 4 .…”
Section: Introductionunclassified